1989
DOI: 10.1177/0893318989002004002
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Communication Efficiency Between High-Impact and Bureaucratic Written Communication

Abstract: Efficient written communications have become increasingly important to public and private sector managers faced with reading an ever-increasing number of documents. This study asseses the communication efficiency associated with two writing styles: a high-impact style and the traditional bureaucratic style still favored by many managers. A total of 262 naval officers stationed at the Pentagon and abroad ships in the San Diego area participated in this study. The results show that the high-impact style takes 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Previous research (Suchan & Colucci, 1989) has shown that readers better comprehend information in HI rather than LI documents. Also, Rogers and Brown (1993) found that readers responding to a HI document better comply with instructions than those reading its LI counterpart.…”
Section: Analysis Of Decision Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research (Suchan & Colucci, 1989) has shown that readers better comprehend information in HI rather than LI documents. Also, Rogers and Brown (1993) found that readers responding to a HI document better comply with instructions than those reading its LI counterpart.…”
Section: Analysis Of Decision Resultsmentioning
confidence: 99%
“…In fact, researchers have even attempted to correlate the readability of a company's annual reports with its financial performance (Courtis, 1986;Jones, 1988;Subramanian, Insley, & Blackwell, 1993). These stud-ies continue despite the large body of research that disputes their value (Selzer, 1981;Stevens, Stevens, & Stevens, 1992;Suchan & Colucci, 1989). Shelby (1992) best summarizes researchers' misgivings about these formulas' value: Readability skeptics believe that formulas tap superficial characteristics of documents; that statistical methodologies are inappropriate for studying writing effects on readers in complex organizational systems; that formulas may correlate with comprehensibility, but they do not predict comprehension ease or difficulty; and that readability is an internal construct existing in the mind of the reader.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For exampie, Kariinsky andKoch (1983), Martindaie, Koch, andKariinsky (1992), and Suchan and Coiucci (1989) use information recaii -the number of correct responses to questions about the information content of documents written in different styies -to measure document effectiveness. This methodology implies that document effectiveness can be measured by readers' relative ability to extract information from, a document and thus correctly respond to questions about it.…”
mentioning
confidence: 99%
“…These factors are important because, as research has shown, they affect readers' ability to process documents efficiently (Felker, Redish, & Peterson, 1985;Guillemette, 1987;Haviland & Clark, 1974;Kieras, 1981;Redish, Battison, & Gold, 1985;Seigel, 1978;Selzer, 1983;Suchan, 1989). However, these studies do not adequately address the complex array of contextual factors that influence a document's creation, and, just as importantly, affect organizational writers' willingness to alter their composing processes and the organization's language norms.…”
Section: Review Of Written Communication Research Conducted Within Ormentioning
confidence: 99%